Doping, performance-enhancing drugs, and hormones in sport : mechanisms of action and methods of detection - Hackney, Anthony C. (Emerging issues in analytical chemistry., 2018)
This book examines the biochemistry and bioanalytical aspects of performance-enhancing drugs (PEDs) and other questionable procedures used by athletes to enhance performance, and informs the specialist and non-specialist of emerging knowledge, techniques, underlying science, and current practice of the discipline.